Analyzing the Cognitive Skill Development of Second Language (L2) Learners through Content and Language Integrated Learning - Imtiaz, Mahrosha; Nazar, Samarah; Hussain, Khadija Ghulam (Pakistan Languages and Humanities Review, 2023)
This study compares CLIL implementation beliefs between content and language teachers, evaluates secondary school students' comprehension using CLIL, and explores CLIL's significance in enhancing cognitive skills. Four private secondary schools in Gujranwala were selected for the research, using questionnaires and interviews for data collection. The study employed Coyle's 4Cs framework. Significant differences were observed between genders in language proficiency development, integration of content and language learning, improvement in critical thinking skills, and the broader implementation of CLIL programs in language education. The research concludes that a better understanding of effective teaching practices in CLIL programs emphasizes the dynamic nature of CLIL teaching, focusing on enhancing language learning experiences and promoting cognitive growth in L2 learners. The recommendations emphasize the importance of inclusive and student-centered approaches in CLIL programs to maximize the benefits for all learners.